The Arctic & Antarctica: Research Questions and Research Timeline. - Neudecker, Mariele (BathSPAdata, 2021)
Two pivotal research trips to Greenland in 2012 and 2015 extended Neudecker’s ongoing research into how the legacy of the Romantic Sublime and limited visual representations shape our perceptions of the Arctic regions. Questioning notions of wilderness in the context of current environmental and geopolitical realities this collection generates new perspectives on the Contemporary Sublime. This item contains Research Questions and a Research Timeline for The Arctic and Antarctica by Mariele Neudecker.